Rekonstruksi Kritis Metode Pembelajaran Sosiologi Berbasis Mazhab Humanistik di Lombok Timur - Abdul Azizurrahman; Abdullah Muzakar (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
The purpose of this study was to examine the implementation of sociology learning in East Lombok Regency and to critically reconstruct sociology learning methods based on the humanistic school of thought in East Lombok Regency. This study was descriptive-qualitative. The location was East Lombok Regency, which has the largest number of high schools in West Nusa Tenggara (NTB) province. Informant collection used a purposive sampling method. Data collection employed documentation, observation, and in-depth interviews. Analysis employed the Miles-Huberman interactive model. The results showed that all learning methods have advantages and disadvantages; none is superior to the other. Furthermore, there is a gap between the conception of sociology learning methods and their implementation in high schools in East Lombok Regency. However, learning success is largely determined by the individual characteristics of students and teachers, who possess free will. In other words, learning methods are one variable among many that determine learning success. The dominant variables are students and teachers.